2018
DOI: 10.1101/317594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction and Elaboration of Autobiographical Memories from Multiple Visual Perspectives

Abstract: Visual perspective, recalling events from one’s own eyes or from an observer-like viewpoint, is a fundamental aspect of autobiographical memory (AM). Yet, how visual perspective influences the functional mechanisms supporting retrieval is unclear. Here, we used a multivariate neuroimaging analysis to characterize the spatiotemporal dynamics supporting AM retrieval from multiple visual perspectives. Both own eyes and observer perspectives engaged an AM retrieval network (i.e., hippocampus, anterior and posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…The authors interpret this result as implicating the angular gyrus in integrating memory features within an egocentric framework to enable the subjective experience of remembering. Other studies have implicated both the angular gyrus and precuneus in shifting visual perspectives during autobiographical memory (Iriye and Jacques, 2018; St Jacques et al, 2017). Thus, it may be the case that interactions between these regions are important for representing events from an egocentric perspective, with the angular gyrus playing more of a critical role than the precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpret this result as implicating the angular gyrus in integrating memory features within an egocentric framework to enable the subjective experience of remembering. Other studies have implicated both the angular gyrus and precuneus in shifting visual perspectives during autobiographical memory (Iriye and Jacques, 2018; St Jacques et al, 2017). Thus, it may be the case that interactions between these regions are important for representing events from an egocentric perspective, with the angular gyrus playing more of a critical role than the precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite prominent proposals that self-consciousness is an essential part of EM, as argued by Endel Tulving (1,46), the impact of experimental alterations of BSC during encoding on later retrieval processes has only recently been investigated. Thus, behavioral evidence demonstrated that the modulation of BSC, using conflicting multisensory and sensorimotor stimulation, influences EM and spatial memory (47)(48)(49)(50)(51)(52). Although not focusing on BSC framework, the work of St. Jacques and colleagues provided preliminary evidence that BSC may impact EM by showing that the retrieval of an event from a 3PP (compared to 1PP) led to poorer recollection of the sensory and perceptual details experienced at encoding, characterized at the neural level by changes in posterior parietal regions (47,48,(51)(52)(53).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, behavioral evidence demonstrated that the modulation of BSC, using conflicting multisensory and sensorimotor stimulation, influences EM and spatial memory (47)(48)(49)(50)(51)(52). Although not focusing on BSC framework, the work of St. Jacques and colleagues provided preliminary evidence that BSC may impact EM by showing that the retrieval of an event from a 3PP (compared to 1PP) led to poorer recollection of the sensory and perceptual details experienced at encoding, characterized at the neural level by changes in posterior parietal regions (47,48,(51)(52)(53). More recently, other studies showed that events seen from a natural 1PP (54)(55)(56)(57) or with higher body ownership (61), during encoding, were associated with more vivid memories and better memory performance compared to events encoded from the 3PP or without a body view (54)(55)(56)(57).…”
Section: Introductionmentioning
confidence: 99%